2010
DOI: 10.1089/ten.tea.2009.0303
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Adipose-Derived Stem Cells into Contractile Smooth Muscle Cells Induced by Transforming Growth Factor-β1 and Bone Morphogenetic Protein-4

Abstract: Smooth muscle cells (SMCs) play an essential role in maintaining the structural and functional integrity of blood vessel and thus is a critical element for blood vessel construction via tissue engineering approach. Adipose-derived stem cells (ASCs) represent a reliable source of mesenchymal stem cells with multidifferentiation potential. In this study, the feasibility of differentiation of human ASCs (hASCs) into cells with phenotypic and functional properties of SMCs was explored. hASCs isolated from human li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 44 publications
5
80
0
Order By: Relevance
“…TGF-␤ 1 has been reported to induce differentiation of mesenchymal stem cells into SMCs (34,46,63). The present study demonstrated that TGF-␤ 1 increased the expression of the SMC-specific transcription factor myocardin in hASCs.…”
Section: Discussionsupporting
confidence: 66%
“…TGF-␤ 1 has been reported to induce differentiation of mesenchymal stem cells into SMCs (34,46,63). The present study demonstrated that TGF-␤ 1 increased the expression of the SMC-specific transcription factor myocardin in hASCs.…”
Section: Discussionsupporting
confidence: 66%
“…WNT signaling, particularly through the WNT3a ligand, seems to mediate TGFβ-induced mesenchymal fibrogenic responses and loss of adipose tissue in skin fibrosis (Akhmetshina et al, 2012;Wei et al, 2012). Furthermore, the differentiation of adipose-derived stem cells to contractile SMCs has shown to be dependent on TGFβ1 and BMP4 (Wang et al, 2010). Under culture conditions permissive for adipogenesis, skeletal muscle is capable of transdifferentiating to mature adipocytes via PPAR activation and upregulation of lipogenic markers Pparg and C/ebpa (Hu et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue represents an abundant source of mesenchymal stromal cells that possess a high level of plasticity, 10 including differentiation into smooth muscle cells (SMC) 11,12 and show significant potential in cardiac and vascular cell therapies. [13][14][15][16][17][18][19] We and others have shown that isolated ASC phenotypically and functionally overlap substantially with pericytes and SMC.…”
Section: Editorial See P 752 In This Issue See P 751mentioning
confidence: 99%